SOME FACTORS RELATED TO AFLATOXIN CONTAMINATION IN MEDICINAL PLANTS AT NGHE AN TRADITIONAL MEDICINE HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To determine aflatoxin levels in traditional herbal medicines and to analyze factors associated with aflatoxin contamination at Nghe An Traditional Medicine Hospital in 2023.Subjects and methods: The study was conducted on 170 traditional herbal medicine samples included in the list of medicines reimbursed by health insurance at the Pharmacy Department of Nghe An Traditional Medicine Hospital. A descriptive study with analytical components was employed.Results: The overall fungal contamination rate was 33.5%. The overall aflatoxin contamination rate was 9.41%. The proportion of samples contaminated with 1 type of aflatoxin was 56.25%; with 2 types, 31.25%; and with 3 types, 12.5%. Factors associated with aflatoxin contamination included: fungal contamination (OR = 5.165, 95% CI: 1.69-15.70, p < 0.05); contamination with Aspergillus spp. (OR = 4.533, 95% CI: 1.47-13.97, p < 0.05); contamination with other fungal species (OR = 4.704, 95% CI: 1.623-13.636, p < 0.01); Chinese herbal medicines (OR = 7.373, 95% CI: 1.621-33.542, p < 0.01); and herbal samples with aflatoxin levels > 0.5 ppb (OR = 5.268, 95% CI: 1.312-21.299, p < 0.05).Conclusion: There is an association between fungal contamination and overall aflatoxin contamination in traditional herbal medicines (OR = 5.165, 95% CI: 1.69-15.70, p < 0.01). Herbal samples contaminated with fungi have a 5.165-fold higher risk of aflatoxin contamination compared with non-contaminated samples. There is also an association between fungal contamination and aflatoxin contamination in Chinese herbal medicines (OR = 7.373, 95% CI: 1.621-33.542, p < 0.01); contaminated Chinese herbal medicine samples have a 7.373-fold higher risk of aflatoxin contamination compared with Vietnamese herbal medicine samples.
Keywords: Traditional herbal medicines, fungi, aflatoxin